RUSSIAN DRINKING: TOO LATE FOR EMERGENCY MEASURES - Alexander Evgenjevich Kuznetsov (Sovremennye Issledovaniâ Socialʹnyh Problem, 2015)
Russian drinking for the first time demonstrates weakening of specialization in spirits drinking and stabilization of amount drunk. This suggests expectations of drinking qualitative turn, i.e. to consumer’s choice oriented to quality of drinking rather than to quantity, and further to lessening the drinking norm. Experience of wine-drinking countries of Europe and influence of pan-European homogenization of patterns of drinking, favor such a perspective. The marked decrease of drinking norm in wine-drinking countries was achieved with the minimal state intervention. Survey data (n=904) is provided to corroborate the claim that Russian drinking is able to self-regulate. The data witness weak support for government’s measures taken to restrict access to beverages sale in terms of age, time, place, and price; customers are likely to value freedom of choice unbridled. Governmental pursuance of simplistic access-and-pricing restrictive policies recently undertaken, may force Russian drinking back to another cycle of alcoholisation within the old ‘northern’ model. Bootlegging expansion, formerly progressive specialization in spirits drinking, habit of making gross purchases in population are explained by former experiences of coping with deficits, dry campaigns, and traditional culture of religious and secular abstinences. Scarcity of modes of compensatory behaviors and low concern for health also back up the special cultural status of alcohol. Government should seek for positive measures, viz. wider sporting involvement for students and inclusion for disabled to revive the nation’s regard for health and awareness of health-related risks.